Increased CA125 Level in Ovarian Fibroma: Case Report - Sedigheh Ghasemian Dizajmehr; Sharzad Sheikhhasani; Azamsadat Mousavi; Farzaneh Rashidi Fakari; Elham Saffarieh; Mohesn Ghasemian (Mashhad University of Medical Sciences, 2020)
Introduction: Fibroma is a sex cord-stromal tumor of ovary, a benign tumor and due to the source of stromal, it cannot produce CA125. CA125 is produced from epithelial cells of the peritoneum, Pleural, pericardium, endocervix, endometrium and fallopian tubes. In this article, a rare case of fibroma with increased CA125 levels is reported. Case presentation: The patient was a 48-year-old nulligravida woman with regular menstrual cycles, with a history of infertility that had undergoing IVF; during an ultrasound, a left ovarian mass was detected. The mass was solid with size of 160×100×90 mm in the left ovary and due to its association with high ascites, pleural effusion, and high CA125; she was admitted to the Imam Khomeini Hospital of Tehran. Conclusion: Increased CA125 levels and its association with adnexa masses, ascites and pleural effusion are the manifestations of malignant ovarian masses. Increased CA125 is not necessarily associated with malignancy, however, it should be considered as a differential diagnosis of Meigs' syndrome which is associated with benign ovarian fibroma masses. Evaluating the cytology of ascites and sending the mass to the pathology of frozen section during surgery should be used to prevent extensive surgeries and loss of fertility. In this patient, fibrothecoma was diagnosed based on Frozen and fibroma was a definitive diagnosis based on pathology.